PENGARUH ASUHAN KEBIDANAN TERHADAP IBU HAMIL DENGAN PREEKLAMPSIA RINGAN - Amalia, Rizki; Kurniasih, Indah; Aidah, Nur (JURNAL KESEHATAN TERAPAN, 2021)
Background: Mild preeclampsia is established based on the onset of hypertension with dipstick proteinuria (+) or edema after 20 weeks of gestation. Kec. Indralaya Kab. Ogan Ilir 2018. The research method used in this research is the prequosy design experiment. The dependent variable in this study was the incidence of mild preeclampsia. This study used a questionnaire to all pregnant women who came to the Puskesmas at BPM Irma Aryani Kompleks Persada Kec. Indralaya Kab. Ogan Ilir in 2018. With a sample of 10 people. The results of the dependent T-test bivariate analysis showed that there was an effect of care before and after the midwifery care intervention on the incidence of mild preeclampsia. Based on the results of the study, it can be concluded that there is an effect of midwifery care in pregnant women with mild preeclampsia. It is recommended for health workers to further improve services to the community related to prevention and handling of mild preeclampsia. Key words: Preeclampsia in pregnant women